Reference Intervals of Serum Non-Cholesterol Sterols by Gender in Healthy Japanese Individuals - Yoshida, Hiroshi; Tada, Hayato; Ito, Kumie; Kishimoto, Yoshimi; Yanai, Hidekatsu; Okamura, Tomonori; Ikewaki, Katsunori; Inagaki, Kyoko; Shoji, Tetsuo; Bujo, Hideaki; Miida, Takashi; Yoshida, Masayuki; et al. (Journal of Atherosclerosis and Thrombosis, 2020)
Aims: The present study was conducted to establish a practical method for measuring non-cholesterol sterols and reference intervals of serum levels.Methods: Healthy subjects (109 men and 151 women), four patients with sitosterolemia, and 10 heterozygous mutation carriers of ABCG5/ABCG8 genes were investigated. Then, three non-cholesterol sterols (sitosterol, campesterol, and lathosterol) of fasting serum samples were measured via a practical and highly sensitive gas chromatography (GC) method with 0.2 µg/mL as the lower limit of quantification. The coefficient of variation (CV) values for within-run reproducibility were 3.06%, 1.89%, and 1.77% for lathosterol, campesterol, and sitosterol, respectively. The CV values for between-run reproducibility were 2.81%, 2.06%, and 2.10% for lathosterol, campesterol, and sitosterol, respectively.Results: The serum levels of sitosterol and campesterol were significantly higher in women than in men, whereas the serum levels of lathosterol were significantly higher in men than in women. Because of these gender difference, the determination of reference intervals of the three sterol values was performed by considering gender. The reference intervals of sitosterol, campesterol, and lathosterol were 0.99–3.88, 2.14–7.43, and 0.77–3.60 µg/mL in men and 1.03–4.45, 2.19–8.34, and 0.64–2.78 µg/mL in women, respectively. The serum levels of sitosterol and campesterol were higher in patients with sitosterolemia (94.3±47.3 and 66.3±36.6 µg/mL, respectively) than in healthy subjects.Conclusion: These results demonstrate a practical and highly sensitive GC method to measure non-cholesterol sterol levels and gender-segregated reference intervals of sitosterol, campesterol, and lathosterol in Japanese healthy subjects.